Estudo do mecanismo de formação de lascamento em cilindros primeiro intermediärios utilizados em laminadores sendzimir - Angelo Ferreira Costa (2015)
In this work, the causes of failure in the first intermediate rolls used in Sendzimir rolling mills were studied. Samples of two rolls from different suppliers were analyzed. They had similar chemical composition (0.8% C, 1.8% Mo, 1.8% W), differing only in chrome percentage. Samples of the rolls were taken by machining process in the center of the rolls, in a disk format of 10mm thickness, and then divided for analysis of hardness, micro hardness, hardness during grinding and metallographic analysis on optical microscope and on scanning electron microscope. Measurements of hardness and micro hardness showed a variation between the surface and the layer below the surface with a grinding depth of 0.8 mm. The area near the surface of roll 01 presented a hardness of 632 HV, whereas the hardness of roll 02 was 714 HV. Metallographic analysis showed that roll 02 presented higher amounts of inclusions than roll 01, and that the maximum diameter of oxides inclusions was around 9 m. Roll 01 presented carbides of tungsten (W) with a percentage 10 times higher than the matrix, what give us a case of a M6C carbide type. The increase in near-surface compressive stress caused by the martensitic transformation from retained austenite during the work or by the localized plastic deformation in the area near the surface can result in the development of the fatigue cracks, as observed in roll 01. The measurements of hardness and micro hardness showed variation when measured transversely, that is, from work surface to within. Roll 02 presented a variation in the subsurface up to 1 mm depth, being the most likely to the generation of micro cracks and fatigue cracking (Spalling), if there is an accumulation of tension or no correct elimination of the hardened layer. The result of surface hardness variation after grinding stage indicates a management gain related to the consumption of rolls per ton of rolled steel.